Penerapan Metode Bernyanyi Dalam Meningkatkan Penguasaan Mufrodat Dalam Pembelajaran Bahasa Arab AUD - asnawati; Mabruri (LPPM STAI La Tansa Mashiro, 2025)
Arabic language learning methods in early childhood have an important position in developing basic language skills as well as being a means of instilling islamic values from an early age. Howevwr, mastery og mufrodat (arabic vocabulary) at an early agr is still relatively low. The problems that teachers often face are low motivation to learn, boredom quickly, and children's lack of interest in learning. Learning processes that do not utilize creative approaches cause children to be inactive and learning outcomes are not optimal. This research aims to improve young children's mastery of Arabic language through the application of the singing method. The singing method was chosen because it can stimulate various aspects of children's abilities, especially language, social-emotional and cognitive. Through songs, children not only repeat words, but also imitate the pronunciation, recognize the meaning, and remember them through rhythm. The results of the research show that the application of the singing method provides a significant increase in children's ability to master mufrodat. In conclusion, the singing method is proven to be effective and relevant in improving young children's mastery of Arabic language.